Structures and host-adhesion mechanisms of lactococcal siphophages - Spinelli, Silvia; Veesler, David; Bebeacua, Cecilia; Cambillau, Christian (Frontiers in Microbiology, 2014)
The Siphoviridae family of bacteriophages is the largest viral family on earth and comprises members infecting both bacteria and archaea. Lactococcal siphophages infect the Gram-positive bacterium Lactococcus lactis, which is widely used for industrial milk fermentation processes (e.g. cheese production). As a result, lactococcal phages have become one of the most thoroughly characterized class of phages from a genomic standpoint. They exhibit amazing and intriguing characteristics. First, each phage has a strict specificity towards a unique or a handful of L. lactis host strains. Second, most lactococcal phages possess a large organelle at their tail tip (termed the baseplate), bearing the receptor binding proteins and mediating host adsorption. The recent accumulation of structural and functional data revealed the modular structure of their building blocks, their different mechanisms of activation and the fine specificity of their receptor binding proteins. These results also illustrated similarities and differences between lactococcal Siphoviridae and Gram-negative infecting Myoviridae.